Sentiment Analysis on Indonesia Twitter Data Using Naïve Bayes and K-Means Method - Ajib Susanto; Muhammad Atho’il Maula; Ibnu Utomo Wahyu Mulyono; Md Kamruzzaman Sarker (Journal of Applied Intelligent System, 2021)
This study focuses on the analysis of sentiments on Indonesian twitter data. Twitter data on Indonesian simultaneous pilkada used to get its sentiments using Naïve Bayes Classifier method as a method of classification and K-means method to get Label on the data train process. Combining the two methods is expected to get high accuracy results. The results obtained from the research shows a pretty good accuracy of 74.5%.